ANALISIS PENGELOLAAN SAMPAH MEDIS PELAYANAN KESEHATAN PRAKTIK BIDAN SWASTA DI KOTA BANJARBARU - Dewi Mustika; Danang Biyatmoko; Adenan Adenan; Abdul Khair (Universitas Lambung Mangkurat, 2014)
The development of health services is inseparable teething problems in the medical waste management, as well as in private practice midwives in the city Banjarbaru. The purpose of the research to know how the system of management, characteristics and analyze large generation of medical waste management methods, and analyze the influence and relationship education level, knowledge and attitudes of medical waste management system of midwives to practice in the city Banjarbaru. This study is a survey with sample size of the study 84 people . Data were analyzed to compare with No. Kepmenkes . 1204/Menkes/SK/X / 2004 and other relevant literature.The result is a system of medical waste management both in private practice midwives only 45.2% with the characteristics of infectious waste generation is (52.74%), pathological waste (39.59%), sharp waste (3,58%), and pharmaceutical waste (4,10%), large generation average 74.92 kg / day. The level of education and attitude influence in medical waste management system of private practice midwives, variables that are related to education level (p = 0.002) and attitude (p = 0.01), while the level of knowledge was not associated (p = 0.380).